Legal Analysis of Sharia Insurance Dispute Resolution at PT. Asuransi Takaful Indonesia - Maulidya Mora Matondang; Akmaluddin Syahputra; Nawir Yuslem; Iwan Nasution; Sutan Erlambang (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2026)
This study aims to analyze disputes in Shariah Insuranceusing a case study of PT Asuransi Takaful. The focus of the study includes the forms and characteristics of disputes, the factors causing them, dispute resolution mechanisms, compliance with Islamic economic law principles, and the parties' perceptions of fairness. This study uses a qualitative approach with a case study method to explore the phenomenon in depth based on empirical data and a literature review. The research results show that disputes are generally related to claims, such as rejections, late payments, and differences in benefit values. Factors contributing to these disputes include a lack of transparency, low Islamic financial literacy, and weak communication between companies and participants. Dispute resolution mechanisms are mostly conducted through non-litigation channels such as deliberation, mediation, and Islamic arbitration, which align with the principle of reconciliation (islah). However, there remains a gap between the normative principles of Islamic economic law and its implementation in the field. The parties' perceptions of fairness are strongly influenced by the transparency of the process and the quality of communication. This research contributes to enriching the study of Sharia insurance disputes through a more contextual case study approach. Furthermore, it provides practical recommendations for companies, regulators, and academics to improve the effectiveness of fair and sharia-compliant dispute resolution.